Invitro Cytotoxicity of Various Parts of Adhahapushpi (Trichodesma Indicum Linn.R.Br.) Against 3 Cancer Cell Lines (AYUSHDHARA, 2022)
Cancer is a leading cause of death and an important source to the mortality and morbidity worldwide. The management in contemporary medicine is having toxicity to normal cells so the world is looking forward for drugs which are cytotoxic to cancer cells and non toxic to host cells and Medicinal plants are the doing well in this aspect.  Adhahapushpi (Trichodesma indicum Linn.R.Br.)Belonging to Boraginaceae family is traditionally used as anticancer to treat breast cancer. Its cytotoxicity against breast cancer and cervical cancer is proved in previous researches. Objectives: The present study was conducted to evaluate its cytotoxicity against 3 Human cancer cell lines Viz. colon cancer cell line (HCT116), oral cancer cell line (KB) and skin cancer cell line (A375). Method: Alcohol, Methanol and Aqueous extracts of Root, Leaf, Stem and Fruit of Adhahapushpi were used to screen in-vitro cytotoxicity. Cytotoxic effect was analysed by MTT assay.Results: The ethanol Root extract was found to be more cytotoxic in vitro to colon cancer cell line (HCT116) with IC50values 176.5±13.36 µg/ml, ethanol extract of fruit to  oral cancer cell line (KB-3-1) with IC50values 154 ± 3.89 µg/ml and root ethanol extract to skin cancer cell line (A375) with  IC50values 169± 12.09 µg/ml respectively.